Lateral transfer at the gene and subgenic levels in the evolution of eukaryotic enolase - Keeling, Patrick J. (The National Academy of Sciences, 2001)
Enolase genes from land plants and apicomplexa (intracellular parasites, including the malarial parasite, Plasmodium) share two short insertions. This observation has led to the suggestion that the apicomplexan enolase is the product of a lateral transfer event involving the algal endosymbiont from which the apicomplexan plastid is derived. We have examined enolases from a wide variety of algae, as well as ciliates (close relatives of apicomplexa), to determine whether lateral transfer can account for the origin of the apicomplexan enolase. We find that lateral gene transfer, likely occurring intracellularly between endosymbiont and host nucleus, does account for the evolution of cryptomonad and chlorarachniophyte algal enolases but fails to explain the apicomplexan enolase. This failure is because the phylogenetic distribution of the insertions—which we find in apicomplexa, ciliates, land plants, and charophyte green algae—directly conflicts with the phylogeny of the gene itself. Protein insertions have traditionally been treated as reliable markers of evolutionary events; however, these enolase insertions do not seem to reflect accurately the evolutionary history of the molecule. The lack of congruence between insertions and phylogeny could be because of the parallel loss of both insertions in two or more lineages, or what is more likely, because the insertions were transmitted between distantly related genes by lateral transfer and fine-scale recombination, resulting in a mosaic gene. This latter process would be difficult to detect without such insertions to act as markers, and such mosaic genes could blur the “tree of life” beyond the extent to which whole-gene lateral transfer is already known to confound evolutionary reconstruction.